2012
DOI: 10.1007/s00114-012-0984-3
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and behavioral response to ultraviolet radiation in the components of a foliar mite prey–predator system

Abstract: Ambient ultraviolet-B (UVB) radiation impacts plant-dwelling arthropods including herbivorous and predatory mites. However, the effects of UVB on prey-predator systems, such as that between the herbivorous spider mite and predatory phytoseiid mite, are poorly understood. A comparative study was conducted to determine the vulnerability and behavioral responses of these mites to ultraviolet (UV) radiation. First, we analyzed dose-response (cumulative irradiance-mortality) curves for the eggs of phytoseiid mites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…These authors irradiated eggs and mites with UVB lamps at a high intensity, 6.8 W m Ϫ2 , for 30 Ð300 min (Onzo et al 2010), resulting in much higher cumulative doses of UVB (12.2Ð122.4 kJ m Ϫ2 ) than the LD 50 values in phytoseiid mite eggs (Ͻ0.3 kJ m Ϫ2 ; Tachi and Osakabe 2012). If the UVB lamp emitted spectra of relatively broad wavelengths, the tails of spectra below 300 nm would have had deleterious effects on the survival of phytoseiid mites, which is frequently true in such equipment (Tachi and Osakabe 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors irradiated eggs and mites with UVB lamps at a high intensity, 6.8 W m Ϫ2 , for 30 Ð300 min (Onzo et al 2010), resulting in much higher cumulative doses of UVB (12.2Ð122.4 kJ m Ϫ2 ) than the LD 50 values in phytoseiid mite eggs (Ͻ0.3 kJ m Ϫ2 ; Tachi and Osakabe 2012). If the UVB lamp emitted spectra of relatively broad wavelengths, the tails of spectra below 300 nm would have had deleterious effects on the survival of phytoseiid mites, which is frequently true in such equipment (Tachi and Osakabe 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The observed differences in UV avoidance response rates among monochromatic radiation at different wavelengths indicate the capacity of N. californicus females to discern variation in wavelengths of UV radiation, such as UVB from UVA. Tachi and Osakabe (2012) reported that N. californicus escaped from solar UV radiation more quickly than visible radiation. However, UVB recognition by N. californicus has never been reported so far.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations